DESAINER DENGAN MANAJEMEN YANG HAIR - Taswadi Taswadi (Universitas Trisakti, 2008)
AbstractThis book aims to assist the achievement of good results from design.Two main concerns in this book have predominated. First concern, to identijy the management issues and responsibih'ties judged to be mos.t sigm_ficant in influencing the progress and outcomes of design projects. Second, to provide information about appropriate management methods and approaches. It does not to set out to influence how designers use their skills. Even less does it attempt to turn managers into designers. It may lead to a better understanding of what designers actually do. It contains a cross- section of views and advice from more than 40 contributor writers. All expert in design fields AbstrakBuku